Eklamsia sebagai faktor prognosis untuk mortalitas maternal pada pre eklamsia berat - Idhah Lestari; Endah Marianingsih Theresia; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2014)
Maternal mortality in eclampsia in global is about 50,000 per year. This case relates to an increase in maternal mortality in developed countries that is around 0% -1.8% and a high increase reaching 15% occur in developing countries. In the period 2008-2012, the maternal mortality due to preeclampsia in RSUD KRT Setjonegoro Wonosobo increased into 47.92%. Along with an increase in maternal mortality due to preeclampsia, eclampsia is also increased from 13.64% to 18.57%. Objective: to know the risk of eclampsia to maternal mortality in severe preeclampsia in RSUD KRT. Setjonegoro Wonosobo. Research Methods: Survey Research Methods with Case Control design. Subjects are pregnant women with severe preeclampsia in RSUD KRT. Setjonegoro, the data is taken by purposive sampling technique. There are 35 sample cases and 175 control samples. Characteristics comparison test for the research subjects uses independent t-test and chi square. Hypothesis test uses chi square, logistic regression and Mantel-Haenszel test. Results: The incidence of maternal mortality in severe preeclampsia women who had eclampsia is 54.3%. Eclampsia related significantly increases the risk of maternal mortality about 92.37 times the p-value of 0.000 (95% CI 20.58 to 414.63). Other prognostic factors that affect the increase in maternal mortality in severe preeclampsia is heart failure p-value of 0.000 (OR 77.5 95% CI 11.09 to 541.27), renal failure p-value 0.002 (OR 74.34 95% CI 4.58 to 1206.22), pulmonary edema p-value of 0.000 (OR 29.54 95% CI 4.75 to 183.63) and HELLP syndrome p-value of 0.030 (OR 8.35 95% CI 1.23 - 58.96). Conclusion: Eclampsia increases the risk of maternal mortality in severe preeclampsia.